Seasonal variation in aflatoxins levels in edible seeds, estimation of its dietary intake and vitamin E levels from Southern Areas of Punjab, Pakistan - Abdull Razis, Ahmad Faizal; Shehzad, Muhammed Muzammel; Usman, Sunusi; Basheir Ali, Nada; Iqbal, Shahzad Zafar; Naheed, Nadia; Asi, Muhammad Rafique (Multidisciplinary Digital Publishing Institute, 2020)
A total of 779 samples of edible nuts (melon seeds, watermelon seeds, pumpkin seeds, and cantaloupe seeds) from Southern Punjab (Pakistan), were collected during the summer and the winter seasons. The natural occurrence of aflatoxins (AFs) and vitamin E (tocopherols) levels were investigated using HPLC. The results have shown that 180 (43.4%) of samples from the winter season and 122 (33.4%) samples from the summer season were found positive for AFs. Elevated average levels of total AFs (20.9 ± 3.10 μg/kg, dry weight) were observed in watermelon seeds without shell, and the lowest average amount (15.9 ± 3.60 μg/kg) were documented in melon seeds without shell samples from the winter season. An elevated average amount of total AFs 17.3 ± 1.50 μg/kg was found in pumpkin seeds available without a shell. The results have documented a significant difference in total AFs levels in edible seeds available with shells versus without shells (α = 0.05 & 0.01). The highest dietary intake of 6.30 μg/kg/day was found in female individuals from consuming pumpkin seeds (without shell) in the winter season. A value of 3.00 μg/kg/day was found in pumpkin seed without shell in the summer season in female individuals. The highest total tocopherol levels were 22.2 ± 7.70 ng/100 g in pumpkin seeds samples from the winter season and 14.5 ± 5.50 mg/100 g in melon seed samples from the summer season. The variation of total tocopherol levels in edible seeds among the winter and summer seasons showed a significant difference (p ≤ 0.0054), except watermelon seeds samples with non-significant differences (p ≥ 0.183).